Impaired Cell Cycle Progression and Self-Renewal of Fetal Neural Stem and Progenitor Cells in a Murine Model of Intrauterine Growth Restriction - Chou, Fu-Sheng; Chen, Chu-Yen; Lee, An-Chun; Wang, Pei-Shan (Frontiers in Cell and Developmental Biology, 2022)
Individuals with intrauterine growth restriction (IUGR) are at an increased risk for neurodevelopmental impairment. Fetal cortical neurogenesis is a time-sensitive process in which fetal neural stem cells (NSCs) follow a distinct pattern of layer-specific neuron generation to populate the cerebral cortex. Here, we used a murine maternal hypoxia-induced IUGR model to study the impact of IUGR on fetal NSC development. In this model, timed-pregnant mice were exposed to hypoxia during the active stage of neurogenesis, followed by fetal brain collection. In the IUGR fetal brains, we found a significant reduction in cerebral cortical thickness accompanied by decreases in layer-specific neurons. Using EdU labeling, we demonstrated that cell cycle progression of fetal NSCs was delayed, primarily observed in the G2/M phase during inward interkinetic nuclear migration. Following relief from maternal hypoxia exposure, the remaining fetal NSCs re-established their neurogenic ability and resumed production of layer-specific neurons. Surprisingly, the newly generated neurons matched their control counterparts in layer-specific marker expression, suggesting preservation of the fetal NSC temporal identity despite IUGR effects. As expected, the absolute number of neurons generated in the IUGR group remained lower compared to that in the control group due to a reduced fetal NSC pool size as a result of cell cycle defect. Transcriptome analysis identified genes related to energy expenditure and G2/M cell cycle progression being affected by maternal hypoxia-induced IUGR. Taken together, maternal hypoxia-induced IUGR is associated with a defect in cell cycle progression of fetal NSCs, and has a long-term impact on offspring cognitive development.